Problems and promises of innovation: why healthcare needs to rethink its love/hate relationship with the new. (30th March 2011) - Dixon-Woods, Mary; Amalberti, Rene; Goodman, Steve; Bergman, Bo; Glasziou, Paul
Abstract : Innovation is often regarded as uniformly positive. This paper shows that the role of innovation in quality improvement is more complicated. The authors identify three known paradoxes of innovation in healthcare. First, some innovations diffuse rapidly, yet are of unproven value or limited value, or pose risks, while other innovations that could potentially deliver benefits to patients remain slow to achieve uptake. Second, participatory, cooperative approaches may be the best way of achieving sustainable, positive innovation, yet relying solely on such approaches may disrupt positive innovation. Third, improvement clearly depends upon change, but change always generates new challenges. Quality improvement systems may struggle to keep up with the pace of innovation, yet evaluation of innovation is often too narrowly focused for the system-wide effects of new practices or technologies to be understood. A new recognition of the problems of innovation is proposed and it is argued that new approaches to addressing them are needed.